Mechanism Of Actions Of Bilimbi Fractions And Its Natural Compounds In Stimulating Brown Adipocyte Differentiation - Fauzi, Farah Binti Md (2024)
Averrhoa bilimbi, or bilimbi, is one of the medicinal plants in the ayurvedic medicine system with various pharmacological activities. The bilimbi leaves were mainly reported for their traditional uses in treating hyperglycemia, diabetes, and related disorders. In previous studies, hexane bilimbi fractions have demonstrated promising anti-obesity properties by stimulating brown adipocyte differentiation. Similarly, major natural compounds of the bilimbi fractions, including phytol and squalene, have also been reported to possess browning activity. However, our understanding of this mechanism of action is still limited to date. To that end, this study focused on a series of transcriptional and translational studies to elucidate the mechanism of action of bilimbi fractions and their corresponding natural compounds in stimulating brown adipocyte differentiation. In the present study, hexane bilimbi fractions (f7, f8, and f9) and their natural compounds (phytol and squalene) substantially stimulated brown adipocyte differentiation at 50 μg/ml and 100 μm, respectively, on the cell-based assay. Based on qrt-pcr analysis, treatment with bilimbi fractions, phytol, and squalene significantly induced the brown-adipocyte marker genes of ucp-1, prdm16, and pgc1-α. Correspondingly, a higher protein expression of cidea, the brown-adipocyte-specific protein marker, was exhibited on a translational level via immunofluorescence assay. The treatment led to the co- development of myotubes and brown adipocytes upon gene knockdown of prdm16. Interestingly,